Tree-rings mirror management legacy: dramatic response of standard oaks to past coppicing in Central Europe - Altman, Jan; Hédl, Radim; Szabó, Péter; Mazůrek, Petr; Riedl, Vladan; Müllerová, Jana; Kopecký, Martin; Doležal, Jiří (PloS one, 2013)
BACKGROUND: Coppicing was one of the most important forest management systems in Europe documented in prehistory as well as in the Middle Ages. However, coppicing was gradually abandoned by the mid-20(th) century, which has altered the ecosystem structure, diversity and function of coppice woods. METHODOLOGY/PRINCIPAL FINDINGS: Our aim was to disentangle factors shaping the historical growth dynamics of oak standards (i.e. mature trees growing through several coppice cycles) in a former coppice-with-standards in Central Europe. Specifically, we tried to detect historical coppicing events from tree-rings of oak standards, to link coppicing events with the recruitment of mature oaks, and to determine the effects of neighbouring trees on the stem increment of oak standards. Large peaks in radial growth found for the periods 1895-1899 and 1935-1939 matched with historical records of coppice harvests. After coppicing, the number of newly recruited oak standards markedly grew in comparison with the preceding or following periods. The last significant recruitment of oak standards was after the 1930s following the last regular coppicing event. The diameter increment of oak standards from 1953 to 2003 was negatively correlated with competition indices, suggesting that neighbouring trees (mainly resprouting coppiced Tilia platyphyllos) partly suppressed the growth of oak standards. Our results showed that improved light conditions following historical coppicing events caused significant increase in pulses of radial growth and most probably maintained oak recruitment. CONCLUSIONS/SIGNIFICANCE: Our historical perspective carries important implications for oak management in Central Europe and elsewhere. Relatively intense cutting creating open canopy woodlands, either as in the coppicing system or in the form of selective cutting, is needed to achieve significant radial growth in mature oaks. It is also critical for the successful regeneration and long-term maintenance of oak populations.
Keywords: Evropa; dub (rod); zachování přírodních zdrojů; ekosystém; stromy; Trees; Ecosystem; Quercus; Europe; Conservation of Natural Resources